X-ray phase-contrast imaging of the breast - Advances towards clinical implementation - Auweter, S. D.; Herzen, Julia; Willner, M.; Grandl, S.; Scherer, K.; Bamberg, F.; Reiser, M. F.; Pfeiffer, F.; Hellerhoff, K. (British Journal of Radiology, 2014)
Breast cancer constitutes about one-quarter of all cancers and is the leading cause of cancer death in women. To reduce breast cancer mortality, mammographic screening programmes have been implemented in many Western countries. However, these programmes remain controversial because of the associated radiation exposure and the need for improvement in terms of diagnostic accuracy. Phase-contrast imaging is a new X-ray-based technology that has been shown to provide enhanced soft-tissue contrast and improved visualization of cancerous structures. Furthermore, there is some indication that these improvements of image quality can be maintained at reduced radiation doses. Thus, X-ray phase-contrast mammography may significantly contribute to advancements in early breast cancer diagnosis. Feasibility studies of X-ray phase-contrast breast CT have provided images that allow resolution of the fine structure of tissue that can otherwise only be obtained by histology. This implies that X-ray phase-contrast imaging may also lead to the development of entirely new (micro-) radiological applications. This review provides a brief overview of the physical characteristics of this new technology and describes recent developments towards clinical implementation of X-ray phase-contrast imaging of the breast. © 2014 The Authors. Published by the British Institute of Radiology.
CRIS-Team Scopus Importer:2023-03-08